Kritik Ideologis Dalam Pendidikan Islam - Sutikno (Program Studi Pendidikan Agama Islam (PAI) Fakultas Tarbiyah dam Ilmu Keguruan Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2023)
This article focuses on critique of ideology studies which reposition of Islamic education as subject in the hegemony of global capitalism. The urgency of critique of ideologgy just not related to neoliberalist and capitalist education system which is oriented to industrial economy but also implication of humanity in industrialization process since first untill contemporary periods. The critique of ideology in Islamic education oriented to syncronize ideology of aducation, especially Islamic education with pancasila and Islamic humanistic values. This efforts is manifestable through discursive practice of all Islamic education elements. This discursive practice based on pure reason and consciousness which is liberated from instrumental and pragmatical interest. This discursice practice reflects a portrait of democracy that is parallel with pancasila and Islamic values.